The Effectiveness of Cooperative Integrated Reading and Composition (Circ) to Improve the Students Ability in Reading - Etika Ariyani; Hidayati Hidayati (Muhammadiyah University of Mataram, 2021)
This research examines the Cooperative Integrated Reading and Composition (CIRC) to improve the students ability in reading. The population of the research is the second grade students of SMPN I Kediri – West Lombok, West Nusa Tenggara Province. The population consists 120 students. The sample of the study were 30 students which separated into groups, experimental and control group consisting of 15 students for every group. To get the data needed, test instruments in the forms pre and post test were employed. The result of this study found that the students ability using CIRS is higher than the students who did not use CIRC. It shown from the mead deviation score of experimental group was 1429 point and the mean score of control group was 998 point. This fact means that the use of CIRC are improve the students competence in reading effectively. Based on the statistical computation, interval confidence of 0.01 (99 %) , t-test : 4.95 higher than t-table :2.76 and interval confidence of 0.05 (95%) , t-test : 4.95 higher than t-table : 2.05 which is automatically means that the Alternative Hypothesis (Ha) is accepted.